Study on transportation and stress distribution of the overburden rock of gob side entry with cutting top and unloading pressure - Yunlin Shuai; Zhenqian Ma; Xiaolei Feng (Scientific Reports)
Abstract In order to solve the problems of serious deformation and difficult support of roadway surrounding rock in the process of gob-side entry driving, taking 230,708 working face of Huopu Mine as the engineering background, the migration characteristics of overburden rock and the stress distribution of surrounding rock before and after roof cutting in the process of gob-side entry driving were studied by means of theoretical analysis, similar simulation test and field measurement. The results show that: ① the establishment of lateral suspension mechanical model analysis found that, with the increase of coal seam dip angle, the reduction of the coal pillar bearing capacity before and after cutting the top gradually decreases, the dip angle of coal seam is 30°, Compared with the reduction of coal pillar bearing capacity before roof cutting is 2164 KN; with the increase of the overburden rock caving angle, the reduction of the coal pillar bearing capacity before and after cutting the top increases continuously, the caving angle of overburden rock is 63°, Compared with the reduction of coal pillar bearing capacity before roof cutting is 2218 KN. ② After the implementation of roof cutting and cutting off the overhanging roof structure, the stress of the surrounding rock of the coal pillar gang in the roadway has significantly decreased by 18.87%, and the stress of surrounding rock of roadway solid coal gang, roof and floor is reduced by 8.48%,5.79% and 4.81% respectively, which relieved the concentration in the surrounding rock stress of the roadway and improves the stress condition of the roadway. The study concludes that roof cutting can not only change the stress environment of the surrounding rock in the roadway, but also increase the filling degree of the goaf, realizing that the coal pillar and the gangue in the goaf jointly bear the overburden rock pressure, ensuring the stability of the roadway.